Public space: an urban management challenge (2004)
Urban management is a task that must involve the Public concept in its entire dimension: public space, type of life related to it, people that crowds it. This text presents a series of considerations about the problems that urban management has to cope with, when power centralization conditions are present. The role of both, State and society, as well as material conditions and politics, are several of the elements to be considered.